The signs of words in poetic language A reading of examples of the poetry of Dick Al-Jinn Al-Homsi - عباس باسم (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research is an attempt to find out the connotations of words in examples of the poetry of the Homs poet Deek Al-Jinn. When words enter into a composition, they acquire secondary connotations that are different from the fixed lexical connotations when they are single, especially in poetic language. This research aims to reveal the various connotations that the poet wishes to convey to the recipient through the words he uses, their diversity in his poetry, and their relationships with... Some of them, the word in the context becomes effective and influential and performs several functions and different connotations according to the topics it contains, and it performs the interactions that The word, when combined with others, plays an important role in the vitality of vocabulary, and the combination of words within sentences gives them connotations and functions that do not lie in their isolation and makes them effective in producing the text, and a starting point in every reading process aimed at reproduction, and this difference results from the difference between the word In ordinary language and the word as an element in poetic language that raises the creative and suggestive energy of its elements, and thus words become signs that any reader must stop at, to discover what they hide and what connotations they indicate.